A genetic analysis of diapause in crosses of a southern and a northern strain of the cabbage beetle Colaphellus bowringi (Coleoptera: chrysomelidae). Issue 5 (13th May 2014) - Chen, C.; Xiao, L.; He, H.M.; Xu, J.; Xue, F.S.
Abstract: As a consequence of geographical variation in diapause mechanism in the cabbage beetle, Colaphellus bowringi, the southern strains enter diapause as an adult in response to long photoperiod, whereas the northern strains enter diapause in response to temperature. In the present study, we examined the inheritance of diapause by crossing a southern Xiushui strain (XS) with a most-northern Harbin strain (HB). The southern XS strain showed a clear short-day response for the induction of diapause, whereas the most-northern strain entered diapause regardless of photoperiod. Interestingly, the XS×HB progeny showed a short-day response, but the HB×XS progeny had no photoperiodic response, indicating that photoperiodic induction of diapause is influenced by maternal genotype. The incidence of diapause of F1 progeny was intermediate between their parents under short daylengths of 12 and 13 h. However, there was a sexual asymmetry, with the female parent exerting a greater effect on diapause incidence than the male parent, indicating a sex linkage in the inheritance of diapause induction. The χ 2 test in C. bowringi revealed that the inheritance of diapause does not fit an additive hypothesis and also that the capacity for diapause is transmitted genetically (or possibly epigenetically) in a manner of incomplete dominance. These results suggest that a number of genetic factors are associated with differences in diapause capability in this beetle.